HUBUNGAN TINGKAT PENGETAHUAN DENGAN TINDAKAN PERAWAT DALAM PENGELOLAAN SAMPAH MEDIS DI RSU SEMBIRING DELI TUA TAHUN 2018 - Bunga mari Sembiring; Fithri Handayani Lubis (JURNAL KESMAS DAN GIZI (JKG), 2019)
ABSTRACT The hospital is one of health service units that produces medical waste. Medical waste management well be giving effect to health workers, patients and the patient’s family. Toable do medical waste management is needed good knowledge and behavior of nurses. The results of pre study at Sembiring hospital, there are activity of nurses of medical waste management like a needle, spuit, a bandage thrown away without separated. Thepurposes of this study is to know The Relationship The Level Of Knowledge With The Actions Nurse Of Medical Waste Management In Sembiring Hospital Deli tua City. The design of study is qualitative and quantitative. The method use descriptive correlative, with cross sectional approach. The populatin study are all of nurses count 50 persons. The sample wew 44 respondents, taken a sample of 44 respondents with a simple random sampling technique. The instrument study used knowledge questionnaire and questionnaire actions of medical waste management after validity and reability tested. The data then tested with Chi Square test. The result showed that 5 respondents (55,6%) with knowledge isn’t good doesn’t take action and 4 respondents (44,4 %) with that takes action of medical waste management. The result of rank the Chi Square test obtained p value = 0,010 ; α = 0,05. The conclusion of the study there were relationship the level of knowledge with the actions nurse of medical waste management in Sembiring hospital. The higher the nurse’s knowledge about medical waste management, the better the nurse’s actions in managing medical waste.